Portulaca oleracea L. (purslane) extract ameliorates intestinal inflammation in diet-induced obese mice by inhibiting the TLR4/NF-κB signaling pathway - Miao, Lingchao; Cheong, Meng Sam; Zhang, Haolin; Khan, Haroon; Tao, Hongxun; Wang, Yuxiao; Cheang, Wai San (Frontiers in Pharmacology, 2025)
BackgroundPortulaca oleracea L. (purslane) is a dietary plant and a botanical drug with antioxidant, antidiabetic, and anti-inflammatory activities. However, the effects of purslane against intestinal-inflammation-associated obesity are yet to be studied. In the present study, we hypothesized that purslane extract could reduce intestinal inflammation associated with metabolic disorder.ResultsMale C57BL/6J mice were fed a high-fat diet (HFD, 60% kcal% of fat) for a total duration of 14 weeks to establish an obesity model; further, the treatment group was orally administered purslane extract (200 mg/kg/day) during the last 4 weeks. Then, intestinal tissues were detached from the mice for detecting protein expressions through Western blot and immunohistochemical analyses. Pro-inflammatory cytokines were determined using ELISA kits, whereas the components of purslane extract were detected by ultra performance liquid chromatography/electrospray ionization quadrupole time-of-flight mass spectrometry. Chronic oral administration of purslane extract ameliorated colon shortening syndrome and reduced bowel inflammation in HFD-induced obese mice through suppression of the toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF-κB) signaling pathway to downregulate TLR4, myeloid differentiation factor 88 (MyD88), Ser32 phosphorylation of NF-κB inhibitor alpha (IκBα), and Ser536 phosphorylation of NF-κB p65 expression levels, thereby inhibiting the pro-inflammatory cytokines, tumor necrosis factor (TNF)-α and interleukin (IL)-6 levels.ConclusionThe present study supports the anti-inflammatory potential of purslane extract for modulating bowel inflammation under obesity through inhibition of the TLR4/NF-κB signaling pathway.